FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UKM (Studi Kasus UKM di Kecamatan Semarang Barat, Kecamatan Semarang Selatan, dan kecamatan Ngaliyan) - Eko Bambang Hadi Prayitno, 14.05.52.0056; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
This research aims to examine empirically the influence of understanding taxpayers, service tax officials and tax penalties on taxpayer compliance SMEs. The population in this research is the taxpayer of SMEs in the city of Semarang as many as 100 SMEs located in 3 district, namely: South Semarang district, West Semarang district, and district Ngaliyan. The method used is purposive sampling method, that is sample selection method (SEM) of indicator x 5 to 10, where this method select sample from element of population which data is easy to get researcher. Test equipment in this using Classic Asumption Test. The result of this research is the understanding of taxpayers affect the taxpayer SMEs, service tax officials and tax sanctions do not affect the complaince of taxpayers SMEs.Keywords : Understanding Taxpayers, Tax Service Services, Tax Sanctions, and Taxpayer Compliance SMEs.